Challenges and Resources for Nurses Participating in a Hurricane Sandy Hospital Evacuation. Issue 6 (14th August 2017) - VanDevanter, Nancy; Raveis, Victoria H.; Kovner, Christine T.; McCollum, Meriel; Keller, Ronald
Abstract: Purpose: Weather‐related disasters have increased dramatically in recent years. In 2012, severe flooding as a result of Hurricane Sandy necessitated the mid‐storm patient evacuation of New York University Langone Medical Center. The purpose of this study was to explore, from the nurses' perspective, what the challenges and resources were to carrying out their responsibilities, and what the implications are for nursing education and preparation for disaster. Design: This mixed‐methods study included qualitative interviews with a purposive sample of nurses and an online survey of nurses who participated in the evacuation. Methods: The interviews explored prior disaster experience and training, communication, personal experience during the evacuation, and lessons learned. The cross‐sectional survey assessed social demographic factors, nursing education and experience, as well as potential challenges and resources in carrying out their disaster roles. Findings: Qualitative interviews provided important contextual information about the specific challenges nurses experienced and their ability to respond effectively. Survey data identified important resources that helped nurses to carry out their roles, including support from coworkers, providing support to others, personal resourcefulness, and leadership. Nurses experienced considerable challenges in responding to this disaster due to limited prior disaster experience, training, and education, but drew on their personal resourcefulness, support from colleagues, and leadership to adapt to those challenges. Conclusions: Disaster preparedness education in schools of nursing and practice settings should include more hands‐on disaster preparation exercises, more "low‐tech" options to address power loss, and specific policies on nurses' disaster roles. Clinical Relevance: Nurses play a critical role in responding to disasters. Learning from their disaster experience can inform approaches to nursing education and preparation.